Кваліметричний підхід до оцінки факторів, які впливають на експлуатацію зубчатих коліс суднових редукторів - Куриляк, В. В.; Хімічева, Г. І. (НТУ "ХПІ", 2015)
У статті розглянутий кваліметричний підхід до дослідження факторів, які впливають на експлуатаційний ресурс зубчатих коліс суднових редукторів, вузлів та агрегатів. Поставлена задача систематизації дефектів, виявлених в процесі ремонтування зубчатих передач. Проаналізовані технічні причини, які призводять до появлення характерних дефектів з ціллю визначення раціонально-ефективного застосування різного типу зміцнюючих засобів. Також запропонована методика видалення конденсату з зони роботи редуктора за допомогою технічного силікагелю.

In the article qualimetric approach to the study of factors that influence the life of ship reducers, components and assemblies was considered. The task of systematization and analysis of defects discov-ered during repair of ship reducers was set. Technical reasons that lead to the appearance of the characteristic defects with aim of determining rational effective use of various types of tonics were analyzed in the article. The most common reasons that lead to reduction of reducers working life, namely their gear transmissions were mentioned. Also the technique of removing condensate from the area of gear by means of technical silica gel was proposed. The desire to increase the mechanized gear durability court-MIB by further increasing demands for precision geometric were little affective combination of parts, as well as leads to substantial growth of technological difficulties and costs of production. Application of new but high-strength materials for the manufacture of critical parts for judicial mechanisms though it promotes growth static strength, but at the same time accompanied by a significant increase of the cost of technological products.
Qualimetric approach to assessing the factors that affect the operation of cogwheels of ship reducers
Keywords: довговічність; ресурси; дефект; аналіз; систематизація; інформація; конденсат; осушення; силікагель; durability; resource; gear; defect; analysis; condensate; drainage; silica gel